2017
DOI: 10.1515/cclm-2016-0931
|View full text |Cite
|
Sign up to set email alerts
|

Reference ranges of thromboelastometry in healthy full-term and pre-term neonates

Abstract: In conclusion, an enhanced fibrinolytic activity in pre-term neonates was noted. For most EXTEM assay parameters, reference ranges obtained from arterial newborn blood samples were comparable with the respective values from studies using cord blood. Modified reagents, small size samples, timing of sampling, and different kind of samples might account for any discrepancies among similar studies. Reference values hereby provided can be used in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 13 publications
3
37
1
1
Order By: Relevance
“…With the increase in age, the Angle, MA and LY30 values increased and the K value decreased. Results showed that the younger the neonate is, the higher the risk of bleeding, and healthy newborns showed a positive correlation with the speed of starting coagulation, which was consistent with previous reports . In addition, the R value was more prolonged in newborns delivered by caesarean section, indicating a probable higher risk of bleeding by caesarean section.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…With the increase in age, the Angle, MA and LY30 values increased and the K value decreased. Results showed that the younger the neonate is, the higher the risk of bleeding, and healthy newborns showed a positive correlation with the speed of starting coagulation, which was consistent with previous reports . In addition, the R value was more prolonged in newborns delivered by caesarean section, indicating a probable higher risk of bleeding by caesarean section.…”
Section: Discussionsupporting
confidence: 90%
“…Results showed that the younger the neonate is, the higher the risk of bleeding, and healthy newborns showed a positive correlation with the speed of starting coagulation, which was consistent with previous TA B L E 2 Comparing the differences in the reference ranges of TEG parameters determined in this study and provided by manufacturers in evaluating neonatal coagulation reports. 15,20,33 In addition, the R value was more prolonged in newborns delivered by caesarean section, indicating a probable higher risk of bleeding by caesarean section. According to the statistical results, we found that the R value was also related to gender, the R value was more prolonged in girls and they may be at higher risk of bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, clot firmness management, e.g., a reduced A5 FIB and A5 in EXTEM assay (A5 EX ), should precede thrombin generation management, e.g., a prolonged CT EX and CT in INTEM assay (CT IN ). ROTEM reference ranges have been established for several populations of healthy individuals (geographically, US and non- Algorithms for ROTEM-guided management US), neonates, infants, children, adolescents, and adults, as well as for pregnant women (1st-3rd trimester and peri-partum) [37][38][39][40][41][42]. However, the reference ranges describing the 95% prediction interval for a specific population of healthy individuals can be used for orientation only and are not designed to predict bleeding or transfusion requirements.…”
Section: Basic Concepts Of Poc Rotem-guided Blee Ding Management Algomentioning
confidence: 99%
“…In addition, studies attempting to establish normal reference ranges for POC tests have been small 5 and have suggested that differences exist between premature neonates and full-term neonates. 6 Additional experience and larger validation studies with these devices will allow increased comfort and improved utilization. Further trials are needed to determine the role and influence of both simple coagulation tests and POC coagulation tests in their ability to predict the risk of bleeding in children, management, and final outcome.…”
Section: Reply To: Use Of Rotem In Correction Of Unexpected Oozing Inmentioning
confidence: 99%
“…In addition, studies attempting to establish normal reference ranges for POC tests have been small and have suggested that differences exist between premature neonates and full‐term neonates . Additional experience and larger validation studies with these devices will allow increased comfort and improved utilization.…”
mentioning
confidence: 99%